Sistem Atap Rumah Otomatis pada Smarthome dengan Menggunakan Arduino - Andriana Kusuma Dewi; Mokhammad Sholihul Hadi; Syaiful Anwar (Jurnal Teknologi dan Sistem Komputer, 2017)
Development of Smarthome system has many important contributions to make a comfortable house. One of the problems is how to keep the house comfortable without becoming moist and getting enough sunlight. In this study, the roof opening that can automatically provide the supply of sunlight using automated roof opener. Manual control of the tool is using smartphone application that communicates through a Bluetooth HC-05 module. This tool also uses an automatic controller with a raindrop sensor that automatically activated when the raindrops on the sensor panel. In addition, this system also integrates the automatic light-intensity sensor using LDR (Light Dependent Resistor). The result of whole system testing is automatic rooftop opener using Arduino Uno works perfectly as the design that the motor is able to be controlled by smartphone application using serial communication based on Bluetooth so that the rooftop can be opened and closed.